Pengaturan Impor Pangan Negara Indonesia Yang Berbasis Pada Kedaulatan Pangan - Fauzin Fauzin (LPPM Universitas Trunojoyo Madura, 2021)
The basic need that is needed by humans to fulfill their survival is food. Thus the basic needs in a country can be fulfilled by domestic products or foreign products which are commonly known as imports. Fulfilling this need for food is very important and strategic in order to maintain the sovereignty of the country, by not depending on food imports from developed countries. Law Number 18 of 2012 on Food, mandates the objectives of food administration, namely realizing food sovereignty, food self-sufficiency and food security. Therefore, it is necessary to increase the production and productivity of food commodities, especially strategic food in order to meet the needs of the community which are always increasing and directly proportional to the population. The method used is normative legal research.